Sistem Informasi Subak Berbasis Web GIS (Geography Information System) dalam Menunjang Pertanian Berkelanjutan di Kecamatan Kediri, Kabupaten Tabanan - Trigunasih, Ni Made; Pramesti, Anak Agung Istri Agung; Sari, Nyoman Bintang Kartika; Pribadi, Prananda Yogathama (Nandur, 2021)
Subak is defined as a customary law community that has socio-agrarian-religious characteristics. One of the subaks in the Bali area is the subak in Kediri District, Tabanan Regency. This Subak does not yet have the latest information data on sustainable food agriculture. Subak in Kediri District, Tabanan Regency is a subak of LP2B (Sustainable Food Agricultural Land). Subak rice fields, data, and information on subak resources have not been mapped spatially. The subak information system was built using geospatial data obtained through participatory mapping in the field and field surveys. Data from the field was digitized using google satellite imagery through the QGIS application so that the area of each subak was obtained as well as information in the form of a subak database. The results of this analysis will become a database by uploading the data to the internet with the help of the Google Maps Api program. The attributes that will be included in the system include: (1) land resources, consisting of subak identity and land suitability; (2) human resources, consisting of the name of the farmer group, the total number of farmers, the number of sharecroppers, the number of owner farmers, land ownership and names of field extension officers, farmer education; and (3) agricultural resources, consisting of data on plant types, cropping patterns, planting times, types of fertilizers, fertilizer doses, rice varieties, origin of rice seeds, pests and marketing.